Adaptive bilateral control of teleoperators with actuator uncertainty and quantized input - Fujie Wang; Zhi Liu; Yun Zhang (Advances in Mechanical Engineering, 2017)
This article addresses the control and stabilization problem of bilateral teleoperator system with input quantized by the so-called hysteresis-type quantizer, where the joint actuator model, robot dynamics, and kinematics are uncertain. In order to overcome the control issue that only discrete and finite control values can be applied to the robot dynamics, a decomposition-based technique is adopted to cope with the quantized control signals. By incorporating the Nussbaum-gain function to the proposed controller, an adaptive telecontrol scheme together with the parameter updating laws is developed to achieve position and velocity tracking of teleoperator system in the presence time delays without a priori knowledge of actuator and quantizer model parameters, upon which, the robot dynamics and kinematics uncertainties are also effectively accommodated. It is proven by the Lyapunov method that the closed-loop dynamics are bounded, and the position as well as velocity tracking errors converges to zero. Simulation results verify the proposed adaptive telecontrol scheme.